Promotion of Reading Interests in the Study Process at the University and Lessons in School - Ausekle, Dagmāra; Kangro, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The necessity of promoting reading interests in connection with the problems that have to be solved today and in near future in school, university and the society on the whole puts forward the task for the prospective teachers of literature to master not only theoretical knowledge in their study process but also to acquire skills necessary for their future pedagogical work so that they are able to choose the most suitable methodological approach for the interpretation of a literary work in each teaching/learning situation.